Religion and transnational citizenship in the African diaspora - Fumanti, Mattia, author.
1 online resource (viii, 195 pages)
Keywords: "This book focuses on Akan speaking Ghanaians in London and explores in detail the experience of African migrants living in Britain, investigating how they construct their British citizenship through their membership of the church. Building on extensive ethnographic research in London and Ghana, the author explores the relationship between religion and citizenship, the emergence of transnational subjectivities, and the making of diaspora aesthetics among African migrants. Starting from the understanding that citizenship is dialogical, a status mediated by a subject's multiple and intersecting identities, the author highlights the limitations of existing conceptualizations of migrant citizenship. Anchored in a case study of the British/Ghanaian Methodist church as a transnational religious organisation and cultural polity, the book explores diasporic religious subjectivities as both cosmopolitan and transnational, while being configured in emotionally and morally significant ways by the Methodist church, as well as family, ethnicity, and nation. Interdisciplinary by nature, this book will be of interest to a wide range researchers and scholars across the social sciences and humanities working in the fields of anthropology, religion, sociology, postcolonial studies, and African studies, and additionally policy makers interested in diaspora and migration studies"--